Knowledge transfer in an architecture firm A case study of millennials’ critical factors during the onboarding process. - CALATRAVA CASTAGNETTI, MARIANGELA (My University, 2020)
The literature indicates the relevance of companies’ initiatives for the learning and integration of newcomers, namely the onboarding process (OP). During the first year of work, when the OP takes place, employees decide if they will leave a company or not. Employees’ turnover represents a knowledge and investment loss for companies, and millennials (1981-1996) tend to leave their job after 2 years because of their values and motivation; this will represent a problem because by 2020 millennials will become the biggest work force. By analyzing the OP from a knowledge management (KM) perspective, this study evaluates two critical factors of millennials in the architecture and construction field, i.e. job satisfaction and retention, with the objective of finding the correlation between the OP tools and practices and these critical factors. The research consisted in a literature review, a factor analysis to determine the work motivation factors (WMFs) that lead to job satisfaction, and a case study of an architecture firm (AFirm) in which thirteen semi-structured interviews were conducted and company documents were analyzed. The findings show that the OP can be interpreted as a knowledge management system (KMS) that takes place within a community of practice (CoP). This KMS allows the transfer of knowledge to new employees, which enables their development and identity building as CoP members, consequently affecting their job satisfaction and retention. Furthermore, the new employees’ identity building, job satisfaction and retention were found to be affected by the following: barriers for newcomers’ participation in the CoP and knowledge transfer (KT); a substitution effect that permits to fix the failure of certain tools and practices; as well as by a corroboration process that leads to newcomers’ verification of the WMFs. Additionally, a correlation between job satisfaction and new employees’ intentions to remain in their job was found, in which organizational support played the most significant role. This research contributes by bringing a new perspective to onboarding from the KM field, emphasizing a link that was seldom considered (i.e. OP and KM); and by suggesting recommendations for AFirm’s OP.
Keywords: Knowledge; Management; Transfer; Tools; Practices; CoP; Onboarding; Millennials; Job satisfaction; Motivation factors; Retention; Turnover; Architecture firms